2022
DOI: 10.4236/health.2022.146051
|View full text |Cite
|
Sign up to set email alerts
|

Ever Use of Modern Contraceptive among Adolescents in Uganda: A Cross-Sectional Survey of Sociodemographic Factors

Abstract: Background: Six in ten sexually active adolescent women in Uganda have an unmet need for contraception yet there is limited data on what is driving its use. This study aimed to determine the associations between sociodemographic factors and modern contraceptive ever-use among adolescents in Uganda. Methods: A crossectional study was conducted among 337 adolescents aged 13 -19 years who had ever had sex in Wakiso (urban) and Kamuli (rural) districts in Uganda. The outcome of interest was the ever-use of modern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Our study further found current use modern contraceptive to be 58.5% among the young people which was higher than that previously reported among adolescents in Uganda at 30.9% (27). The higher prevalence of modern contraceptive use in this study is likely due to increased knowledge (28).…”
Section: Discussionsupporting
confidence: 46%
“…Our study further found current use modern contraceptive to be 58.5% among the young people which was higher than that previously reported among adolescents in Uganda at 30.9% (27). The higher prevalence of modern contraceptive use in this study is likely due to increased knowledge (28).…”
Section: Discussionsupporting
confidence: 46%
“…Additionally, only 7% of them used family planning within the first six months after giving birth [1,9]. Use of family planning services is seen as entirely female's duty in much of the world, although it is a dual commitment Men are mostly forgotten by health clients, particularly in case of family planning services ( [1,10]. Globally according to WHO Report [11], annually, over 9 million teenage adolescents give birth as results of unmet needs of their reproductive plans and this is a worrisome concern for the policy makers, demographers, health specialists, social scientists as well as the public.…”
Section: Issn: 2579-0730 ©Idosr Publicationsmentioning
confidence: 99%